2021
DOI: 10.3389/fonc.2021.655826
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Nomogram to Predict Early Death in Advanced Epithelial Ovarian Cancer

Abstract: Background: Ovarian cancer is a common gynecological malignancy, most of which is epithelial ovarian cancer (EOC). Advanced EOC is linked with a higher incidence of premature death. To date, no effective prognostic tools are available to evaluate the possibility of early death in patients with advanced EOC.Methods: Advanced (FIGO stage III and IV) EOC patients who were enrolled in the Surveillance, Epidemiology, and End Results database between 2004 and 2015 were regarded as subjects and studied. We aimed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…30 Additionally, the relationship between risk for early death and age differs with tumor types. 12,19 Our study found that both chemotherapy and radiotherapy were powerful protective factors for early death, as reported by other researchers. 29,31,32 Moreover, a recent study demonstrated that chemoradiotherapy was superior to radiotherapy alone in elderly EC patients.…”
Section: Discussionsupporting
confidence: 86%
“…30 Additionally, the relationship between risk for early death and age differs with tumor types. 12,19 Our study found that both chemotherapy and radiotherapy were powerful protective factors for early death, as reported by other researchers. 29,31,32 Moreover, a recent study demonstrated that chemoradiotherapy was superior to radiotherapy alone in elderly EC patients.…”
Section: Discussionsupporting
confidence: 86%
“…Analysis using the C-index suggests that continuous LODDS and continuous LNR were superior, having the strongest predictive accuracy for both overall survival and cancer-specific survival. Previous studies have shown that prognostic nomograms can be used to facilitate prognostic assessments and can be used to develop more personalized care ( 30 , 31 ). In this study, calibration curves for 3- and 5-year survival and CSS matched well with the ideal line.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with existing nomograms to predict death risk in ovarian cancer, our nomogram included tumor size, residual size of cancer foci, and surgery of primary site, which are consistent with the factors affecting the prognosis of death risk in ovarian cancer, as discussed by Mosgaard et al [ 6 ]. A recent article on ED in ovarian cancer studied advanced EOC (FIGO stages III and IV) [ 22 ]. However, our research included data on various stages of ovarian cancer, especially postoperatively.…”
Section: Discussionmentioning
confidence: 99%